2018
DOI: 10.1101/370536
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell-type specific D1 dopamine receptor modulation of projection neurons and interneurons in the prefrontal cortex

Abstract: Dopamine modulation in the prefrontal cortex (PFC) mediates diverse effects on neuronal physiology and function, but the expression of dopamine receptors at sub-populations of pyramidal neurons and interneurons remains unresolved. Here, we examine D1 receptor expression and modulation at specific cell types and layers in the mouse prelimbic PFC.We first show that D1 receptors are enriched in pyramidal neurons in both layers 5 and 6, and that these cells project intra-telencephalically, rather than to sub-corti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 122 publications
4
19
0
Order By: Relevance
“…As reported here, D1 receptor activation increased the amplitude of EPSPs evoked in both subtypes of layer V pyramidal cells by direct layer V stimulation. The similar effects of D1 receptor activation that we observed support the idea that the majority of commissural fibers is targeting layer V. Furthermore, Anastasiades et al () have also reported that D1 receptor activation enhances cortico‐cortical connectivity, supporting the results reported here. Contrary to results reported here, others have shown that D1 receptor activation suppresses commissural fiber‐evoked EPSCs in layer V pyramidal cells through a presynaptic mechanism involving modulation of calcium channels (Burke et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As reported here, D1 receptor activation increased the amplitude of EPSPs evoked in both subtypes of layer V pyramidal cells by direct layer V stimulation. The similar effects of D1 receptor activation that we observed support the idea that the majority of commissural fibers is targeting layer V. Furthermore, Anastasiades et al () have also reported that D1 receptor activation enhances cortico‐cortical connectivity, supporting the results reported here. Contrary to results reported here, others have shown that D1 receptor activation suppresses commissural fiber‐evoked EPSCs in layer V pyramidal cells through a presynaptic mechanism involving modulation of calcium channels (Burke et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…However, further exploration would be warranted to make definitive conclusions regarding the mechanism of D1R‐induced burst generation. Since many commissural fibers synapse on basal dendrites of IT and PT cells within layer V (Dembrow et al, ; Anastasiades et al, ), and D1 receptors are more abundant within the deep cortical layers (Gaspar et al, ; Scheler and Fellous, ; Anastasiades et al, ) our data suggest that D1 receptor activation may promote burst firing initiated by enhancing basal synaptic input. Whether this effect is limited to commissural fiber activation is currently unknown, and whether the effect has any physiological significance requires further studies.…”
Section: Discussionmentioning
confidence: 58%
“…It has been suggested that in the neocortex, the laminar position of a neuronal cell body accounts for the differences in connection probability and short-term synaptic dynamics (Lefort and Petersen 2017;Seeman et al 2018;Frandolig et al 2019). However, for an in-depth understanding of the organization of intra-laminar connectivity in the neocortex a thorough classification of the neuronal cell types in a given cortical layer is crucial (Kiritani et al 2012;Kawaguchi 2017;Anastasiades et al 2019;Whitesell et al 2020). In previous studies of L6A microcircuits CCla PCs were often overlooked (West et al 2006;Crandall et al 2017;Sundberg et al 2018;Frandolig et al 2019), probably because of their low density and their differential laminar distribution in various cortical areas (Gutierrez-Lbarluzea et al 1999;Wang et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Striatal neurons respond to sensory input from different modalities including tactile, auditory, and visual input (Reig and Silberberg 2014). Pyramidal cells projecting to the striatum are distributed throughout layer 2 to 6 (Anastasiades et al 2019;Zhang et al 2019). Because the density of corticostriatal PCs is particularly high in cortical layer 5 most studies have focussed on these neurons (Shepherd 2013).…”
Section: Putative Cortico-claustral Pcsmentioning
confidence: 99%
“…Growing evidence indicates that distinctions in molecular (e.g., ion channels, receptors), neurophysiology, and anatomical connectivity endow specific subpopulations of PYR with unique properties to integrate input and communicate information downstream ( Brown and Hestrin, 2009 ; Degenetais et al, 2002 ; Dembrow et al, 2010 ; Gee et al, 2012 ; Kim et al, 2016 ; Seong and Carter, 2012 ; Sohal et al, 2009 ; Yang et al, 1996 ). For example, recent evidence indicates that PYR neurons expressing either the dopamine D1 (D1-PYR) or D2 (D2-PYR) receptor exhibit distinctions in spike firing, ion channel expression and conductance, inhibitory synaptic innervation, and subcortical projection targets, that likely define how they contribute to behavior and undergo experience-induced plasticity (e.g., stress) ( Anastasiades et al, 2018 ; Benes et al, 1993 ; Gee et al, 2012 ; Santana et al, 2009 ; Seong and Carter, 2012 ; Xu and Yao, 2010 ). As these cortical networks likely provide a neuroanatomical framework for complex regulation of behavior ( Brumback et al, 2018 ; Gaspar et al, 1995 ; Gee et al, 2012 ; Jenni et al, 2017 ; Santana et al, 2009 ; Seong and Carter, 2012 ; Vincent et al, 1993 ), a critical step towards understanding how stress influences behavior include identifying the selectivity of stress-induced plasticity and associated mechanisms ( Jenni et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%